2004
DOI: 10.1038/sj.cdd.4401432
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms promote the inhibition of classical nuclear import upon exposure to severe oxidative stress

Abstract: In growing HeLa cells, severe stress elicited by the oxidant hydrogen peroxide inhibits classical nuclear import. Oxidant treatment collapses the nucleocytoplasmic Ran concentration gradient, thereby elevating cytoplasmic GTPase levels. The Ran gradient dissipates in response to a stress-induced depletion of RanGTP and a decreased efficiency of Ran nuclear import. In addition, oxidative stress induces a relocation of the nucleoporin Nup153 as well as the nuclear carrier importin-b, and docking of the importin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 44 publications
3
131
2
Order By: Relevance
“…Oxidative and UV stress have both been shown to cause Ran delocalization (Czubryt et al, 2000;Kodiha et al, 2004;Miyamoto et al, 2004). It has recently been reported that the Ran delocalization in response to oxidative stress induced by hydrogen peroxide is due to a stress-induced drop in ATP levels (Yasuda et al, 2006) However, our measurements of nucleotide levels during osmotic stress showed that Ran relocalization does not strictly correlate with changes in energy levels in the cell.…”
Section: The Ran Protein Gradient Is Not Strictly Dependent On Guanincontrasting
confidence: 52%
“…Oxidative and UV stress have both been shown to cause Ran delocalization (Czubryt et al, 2000;Kodiha et al, 2004;Miyamoto et al, 2004). It has recently been reported that the Ran delocalization in response to oxidative stress induced by hydrogen peroxide is due to a stress-induced drop in ATP levels (Yasuda et al, 2006) However, our measurements of nucleotide levels during osmotic stress showed that Ran relocalization does not strictly correlate with changes in energy levels in the cell.…”
Section: The Ran Protein Gradient Is Not Strictly Dependent On Guanincontrasting
confidence: 52%
“…In addition, there were no gross morphological or structural differences in crosssections between nuclear envelopes of mock and HIV-1-expressing cells. 7 In software-generated surface renditions, the dramatic increase in abundance of Nup62 staining at the nuclear envelope and its spreading into the nuclear matrix may represent signals from the recognition of full-length and several proteolytic products of Nup62 by our two antibodies, as suggested (72,78). This observation would be in line with earlier siRNA-mediated Nup62 depletion studies (79) and was partly explained by the authors as a preferential replenishment of Nup62 at the nuclear pore complex, a phenomenon that may be occurring in HIV-1-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…26 Conversely, in response to external stimuli triggering apoptosis, a change in the RanGTP/RanGDP gradient is observed, leading to the inhibition of active nuclear transport. 7,9 In this study, using trypanosomatid protozoa, we have (i) identified Ran and several of its main partners in this divergent cell model, (ii) specified their subcellular localisation at the NPCs and (iii) characterized the apoptotic phenotypes induced by the depletion of their expression.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, the reduction of importin-b and importin-a3 levels leads to an increase in the number of apoptotic cells. 6 Besides, intracellular redistribution of nucleocytoplasmic transport factors is an early feature of apoptosis, which precedes caspase activation, 1,7 and which has been observed in response to cellular stresses including UV irradiation, oxidative stress and heat-shock 8 and hyperosmotic stress. 9 However, it is our opinion that all these reports do not allow inferring any firm conclusions on the link between the inhibition of the nucleocytoplasmic transport and apoptosis, in view of the diverse and essential functions of the proteins studied.…”
mentioning
confidence: 99%